If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -4 = 12 Reorder the terms: -4 + -8x = 12 Solving -4 + -8x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -8x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + -8x = 12 + 4 -8x = 12 + 4 Combine like terms: 12 + 4 = 16 -8x = 16 Divide each side by '-8'. x = -2 Simplifying x = -2
| 24x^5+52x^4+24x^2=0 | | 3c+19=-2 | | 7(2x-3)=12 | | 90x^2-105x=0 | | 25x+20=30x+5 | | 5q^2-4q-1=0 | | 6x^2+22x-8= | | 9y+1=13 | | -(3v-8)=-23+9v | | 47n^2+48n+1=0 | | 28g^2-343=0 | | f(x)=2x^2-7x-13 | | 2-2y+7t=-9 | | x-(-3)=41 | | 0.5-.625x=.875x+3.5 | | 3h^2-32h-11=0 | | (x+5)(x+2)=26 | | x^2=0.64 | | 3x-4=9x+28 | | (2x+17)-(3x-5)=180 | | 103+6x=1+18x+6 | | 8x-(x-3)=9-(3x+6) | | 7(4x-2)+3.5=59.5 | | 231=2x^2-x | | 19=2(x-4)+26 | | 3x-9(8y+5x)= | | u^2-19u+18=0 | | -6(1-8p)=-6+3p | | -9-4r=5r+9 | | 9x-19x^2-6x+11x^2= | | -4-9m=-5m | | 8n+7(2+8n)=14-2n |